2014
DOI: 10.1016/j.joca.2014.08.015
|View full text |Cite
|
Sign up to set email alerts
|

Identical subchondral bone microarchitecture pattern with increased bone resorption in rheumatoid arthritis as compared to osteoarthritis

Abstract: Apart from higher bone resorption in the general subchondral bone of RA samples, the peri-articular bone exhibited similar microarchitectural and bone remodeling characteristics in RA and OA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 50 publications
1
24
0
Order By: Relevance
“…This phenotype was consistent with data reported by a recent study, which identified a more sclerotic phenotype in the trabecular bone surrounding the subchondral bone edema/lesion compared to the trabecular bone distant to the edema/lesion in femoral heads from patients with RA. (46) The sclerotic phenotype in RA-affected subchondral bone may involve the in situ osteoblastic commitment of those MSCs/osteoprogenitors aggregating in the bone marrow as the disease progresses.…”
Section: Discussionmentioning
confidence: 99%
“…This phenotype was consistent with data reported by a recent study, which identified a more sclerotic phenotype in the trabecular bone surrounding the subchondral bone edema/lesion compared to the trabecular bone distant to the edema/lesion in femoral heads from patients with RA. (46) The sclerotic phenotype in RA-affected subchondral bone may involve the in situ osteoblastic commitment of those MSCs/osteoprogenitors aggregating in the bone marrow as the disease progresses.…”
Section: Discussionmentioning
confidence: 99%
“…All specimens comprised the subchondral trabecular bone (STB) and deeper trabecular bone (DTB). STB is defined as the most superficial 5 mm of the trabecular cylinder immediately under cartilage and subchondral cortical bone [22][23][24], while DTB is defined as the deepest 5 mm of the cylindrical specimen. Specimens were fixed in 4% paraformaldehyde in PBS for 5 days and stored in 70% ethanol.…”
Section: Specimen Preparationmentioning
confidence: 99%
“…This meta‐analysis points to the existence of a robust cross‐talk between subchondral bone and articular cartilage underlying joint diseases . Shared features in patients with rheumatoid arthritis and osteoarthritis include not only subchondral bone resorption but also microarchitecture and periarticular bone remodeling, including the subchondral bone …”
Section: Cross‐talk Between Articular Cartilage and Subchondral Bone mentioning
confidence: 89%
“…In these conditions, and unlike what occurs physiologically, one sees not a single electrical pulse (spike), but rather a series of pulses. Consequently, the threshold of neuronal activation is lowered and the neuron now becomes receptive to stimuli not normally painful (allodynia), an indication of peripheral sensitization …”
Section: Articular Mast Cellsmentioning
confidence: 99%
See 1 more Smart Citation